Necessary conditions for establishing an international financial center in Asia - Thang Cong Nguyen; Nhan Thien Nguyen; Duc Hong Vo (Cogent Business & Management, 2020)
Establishing an international financial center appears to be an important goal of many governments in emerging markets in Asia to support national economic growth. The establishment of such a center requires a multifaceted approach in which theoretical and practical aspects are important to consider. This study is conducted to examine and identify the necessary conditions leading to the establishment of a center in the Asian region. We identify 14 determinants in the current literature. We then construct 16,384 models to consider the relevance and importance of each of these 14 determinants in the context of the Asian region. The Bayesian averaging of classical estimates (BACE) is used with a sample of 35 Asian countries in this paper. Findings from our paper indicate that emerging and developing countries in the Asian region should focus on the following fundamental determinants: freedom to trade internationally, market size, higher education and training, and the size of the government. Policy implications are offered based on our findings.
Keywords: 650; freedom to trade; market size; higher education and training; government size; Bayesian averaging of classical estimates; Asian region